Sexual activity and sexual dysfunction of women in the perinatal period: a longitudinal study - Wallwiener, Stephanie; Marshall, Anne; Kuon, Ruben-Jeremias; Feller, Sandra; Wallwiener, Markus; Matthies, Lina (Archives of gynecology and obstetrics, 2017)
PurposeReduced sexual activity and dysfunctional problems are highly prevalent in the perinatal period, and there is a lack of data regarding the degree of normality during pregnancy. Several risk factors have been independently associated with a greater extent of Female Sexual Dysfunction (FSD). Therefore, this study aimed to assess the prevalence of sexual inactivity and sexual dysfunctions in German women during the perinatal period and the verification of potential risk factors.MethodsQuestionnaires were administered to 315 women prenatally (TI 3rd trimester) and postpartum (TII 1 week, TIII 4 months), including the Female Sexual Function Index (FSFI), the Edinburgh Postnatal Depression Scale (EPDS), and the Questionnaire of Partnership (PFB).ResultsThe frequency of sexual inactivity was 24% (TI), 40.5% (TII), and 19.9% (TIII). Overall, 26.5−34.8% of women were at risk of sexual dysfunction (FSFI score <26.55) at all measurement points. Sexual desire disorder was the most prevalent form of Female sexual dysfunction. Furthermore, especially breastfeeding and low partnership quality were revealed as significant risk factors for sexual dysfunctional problems postpartum. Depressive symptoms having a cesarean section and high maternal education were correlated with dysfunctional problems in several subdomains.ConclusionsFindings indicated that women at risk of FSD differed significantly in aspects of partnership quality, breastfeeding, mode of delivery, maternal education, and depressive symptoms. Aspects of perinatal sexuality should be routinely implemented in the counseling of couples in prenatal classes.
Gesehen am 31.10.2018